Optimal sowing dates of three species of grain-bearing amaranth in the semi-arid Argentine Pampa - De Troiani, M.R.=700 1 Sanchez, T.M.; Reinaudi, N.B.; De Ferranola, L.A.
(Es, En)
ilus., 23 ref.
Keywords: AMARANTHUS CRUENTUS; GRANOS; PRODUCCION; RENDIMIENTO; ESPAÑA; AMARANTO